Development of a Raspberry Pi-Based Wireless Educational Tool - Santillán Carranza, Holger Jorge; Enríquez Sandoval, Jairo Oliver; Bonilla Castro, José Fernando (INGENIO, 2024)
The following document presents an analysis and investigation of a weather system using IoT and Raspberry Pi. The main objective is to demonstrate one of the many applications of new technologies. A small WLAN network is established to connect the weather station's server to a home automation controller using a Raspberry Pi device. This enables the integration of the Internet of Things into the planned system, as well as the collection of data from various sensors in the weather station. Additionally, these data are compared with those obtained by other systems on the web over a period of time, validating the sensors' efficiency with 97.66% accuracy and the accuracy of the collected data. This sets a precedent for future research in the fields of home automation and telecommunications.